1983
DOI: 10.1128/mcb.3.11.2066
|View full text |Cite
|
Sign up to set email alerts
|

Co-amplification of rRNA genes with CAD genes in N-(phosphonacetyl)-L-aspartate-resistant Syrian hamster cells.

Abstract: The amplified CAD genes in N-(phosphonacetyl)-L-aspartate (PALA)-resistant Syrian hamster cells are located in an expanded chromosomal region emanating from the site of the wild-type gene at the tip of the short arm of chromosome B-9. The terminus of B-9 in PALA-sensitive cells contains a cluster of rRNA genes (i.e., a nucleolus organizer, rDNA). We have used a molecular clone containing sequences complementary to Syrian hamster 28S rRNA to investigate whether rDNA is coamplified with CAD genes in the PALA-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…Gene amplification is often accompanied by coamplification of very large stretches of flanking DNA (10,36,38). To investigate whether some or all genes reside on the same amplified unit, we digested the DNA from resistant cells with restriction enzymes that cut infrequently in mammalian DNA and size fractionated the resulting fragments by pulsed field gradient gel electrophoresis (34), which allows separation of very large (100 to 1,000 kb) DNA fragments.…”
mentioning
confidence: 99%
“…Gene amplification is often accompanied by coamplification of very large stretches of flanking DNA (10,36,38). To investigate whether some or all genes reside on the same amplified unit, we digested the DNA from resistant cells with restriction enzymes that cut infrequently in mammalian DNA and size fractionated the resulting fragments by pulsed field gradient gel electrophoresis (34), which allows separation of very large (100 to 1,000 kb) DNA fragments.…”
mentioning
confidence: 99%
“…Indeed, we have found that the majority of TUNEL positive micronuclei are lamin negative ( Figure 3). As nuclear lamins are substrates for the caspases that initiate apoptosis (21,22,23), the data suggest that there is a class of micronuclei that undergoes apoptosis under conditions where the main nucleus has its lamina intact and shows no chromatin condensation or other indications of apoptosis. These preliminary data suggest a new mechanism for localized degradation of nuclear DNA in the cytoplasm that is contained in a defective nuclear membrane.…”
Section: Specific Aim 5 Determining Whether Micronuclei Serve As Tramentioning
confidence: 99%
“…If DMs in tumours encode genes that are rate limiting for cell growth in vivo, as they appear to be in v/'fro 13 "' 3,18 , then their elimination would provide a chemotherapeutic strategy targeted at a specific molecular defect uniquely found in cancer cells 19 ' 20 . This is an attractive possibility as DMs occur frequently in clinically important neoplasms including those of the breast 21 , lung 22 , ovary 23 , and colon 24 . Only a fraction of DMs or HSRs have been shown to contain known oncogenes.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
See 2 more Smart Citations